2022
DOI: 10.3390/ijms23179647
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular Fluorescence Complementation Profiling and Artificial Intelligence Structure Prediction of the Kaposi’s Sarcoma-Associated Herpesvirus ORF18 and ORF30 Interaction

Abstract: Kaposi’s sarcoma-associated herpesvirus (KSHV) is the etiologic agent of Kaposi’s sarcoma, primary effusion lymphoma (PEL), and multicentric Castleman’s disease. During KSHV lytic infection, lytic-related genes, categorized as immediate-early, early, and late genes, are expressed in a temporal manner. The transcription of late genes requires the virus-specific pre-initiation complex (vPIC), which consists of viral transcription factors. However, the protein-protein interactions of the vPIC factors have not bee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…Prediction structure models by the deep-learning algorithm have been widely used as powerful tools for life-science fields, including virology. We previously applied that to a partial vPIC protein-protein interaction model (28). The structure of KSHV ORF34 is predicted by Alphafold2, an algorithm for predicting the protein structure from the amino-acid sequence (29).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prediction structure models by the deep-learning algorithm have been widely used as powerful tools for life-science fields, including virology. We previously applied that to a partial vPIC protein-protein interaction model (28). The structure of KSHV ORF34 is predicted by Alphafold2, an algorithm for predicting the protein structure from the amino-acid sequence (29).…”
Section: Resultsmentioning
confidence: 99%
“…Pull-down assays between the vPIC components and ORF34 were performed as described previously (20, 23, 28). In brief, 293T cells were transfected with the indicated plasmids using PEI-MAX (46) and cultured for two days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From 2015, there has been an exponential increase in the number of publications that use deep learning in the pathology field in Japan. Examples include gastrointestinal pathology, 122 precision medicine, 123 urothelial carcinoma, 124 ocular pathology, 125 esophageal cancer, 126 lung cancer, 127 thyroid cytology, 128 intestinal diseases, 122,[129][130][131][132][133][134][135] sarcoma, 136 hematological, [137][138][139][140] among others. In the field of malignant lymphoma, Miyoshi H and Ohshima K et al showed how deep learning was capable of high-level computer-aided diagnosis based on H&E slides, including diffuse large B-cell lymphoma, follicular lymphoma, and reactive lymphoid hyperplasia; 141 and Hashimoto N and Takeuchi I et al analyzed several malignant lymphoma cases using immunohistochemical patterns.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…However, the nature of the protein-protein interaction of the vPIC factors has not been completely elucidated. Maeda et al characterized the interaction of vPIC factors ORF18 and ORF30 using a bimolecular fluorescence complementation assay, a pull-down assay, and an AlphaFold2 predicted binding model [14]. As a result, they identified four amino acid residues (Leu29, Glu36, His41, and Trp170) of ORF18 that were responsible for its interaction with ORF30.…”
mentioning
confidence: 99%